Selection of optimal reference genes for gene expression studies in chronically hypoxic rat heart - Benak, Daniel; Sotakova-Kasparova, Dita; Neckar, Jan; Kolar, Frantisek; Hlavackova, Marketa (Molecular and cellular biochemistry, 2019)
Adaptation to chronic hypoxia renders the heart more tolerant to ischemia/reperfusion injury. To evaluate changes in gene expression after adaptation to chronic hypoxia by RT-qPCR, it is essential to select suitable reference genes. In a chronically hypoxic rat model, no specific reference genes have been identified in the myocardium. This study aimed to select the best reference genes in the left (LV) and right (RV) ventricles of chronically hypoxic and normoxic rats. Sprague-Dawley rats were adapted to continuous normobaric hypoxia (CNH; 12% O2 or 10% O2) for 3 weeks. The expression levels of candidate genes were assessed by RT-qPCR. The stability of genes was evaluated by NormFinder, geNorm and BestKeeper algorithms. The best five reference genes in the LV were Top1, Nupl2, Rplp1, Ywhaz, Hprt1 for the milder CNH and Top1, Ywhaz, Sdha, Nupl2, Tomm22 for the stronger CNH. In the RV, the top five genes were Hprt1, Nupl2, Gapdh, Top1, Rplp1 for the milder CNH and Tomm22, Gapdh, Hprt1, Nupl2, Top1 for the stronger CNH. This study provides validation of reference genes in LV and RV of CNH rats and shows that suitable reference genes differ in the two ventricles and depend on experimental protocol.
Keywords: Chronic hypoxia; mužské pohlaví; Male; Left ventricle; chronická nemoc; Heart Ventricles; regulace genové exprese; referenční standardy; Chronic Disease; myokard; RT-qPCR; srdeční komory; Reference Standards; Rat; Animals; Myocardium; Reference genes; zvířata; hypoxie; Heart; Hypoxia; Rats, Sprague-Dawley; Gene Expression Regulation; potkani Sprague-Dawley